The American journey - Appleby, Joyce Oldham; Brinkley, Alan; McPherson, James M. (Glencoe, McGraw-Hill, 2006)
The American Journey: Reconstruction to the Present is the last half of The American Journey and begins in 1864 (Unit 6). There is a two chapter review Prologue from pre-exploration to Reconstruction. The Declaration of Independence, The United States Constitution, and the Citizenship Handbook are also included. Paired with The American Republic to 1877, the two books create a seamless two-year scope and sequence for middle school. Its unparalleled author team, including the National Geographic, ensures accuracy in every detail of the narrative, maps, and charts. Features: Accessible reading and reading strategies are a priority.Exclusive! Foldables - student-made three-dimensional graphic organizers - are a unique strategy that helps students read effectively and also can be used as assessment or study tools. A Guide to Reading, Reading Checks, and a Summary in every chapter keep students on track as they learn to read for information and process what they''ve read.The extensive use of graphics, maps, and photography creates a visual/verbal approach that appeals to all of your students.